Hemosiderin-Laden Macrophages in Bronchoalveolar Lavage: Predictive Role for Acute Exacerbation of Idiopathic Interstitial Pneumonias - Toru Arai; Tomoko Kagawa; Yumiko Sasaki; Reiko Sugawara; Chikatoshi Sugimoto; Kazunobu Tachibana; Yoshiki Fujita; Seiji Hayashi; Yoshikazu Inoue (Canadian Respiratory Journal)
Background. Hemosiderin-laden macrophages (HLMs) have been identified in the bronchoalveolar lavage fluid (BALF) of patients with idiopathic pulmonary fibrosis (IPF). This retrospective study examined the ability of HLMs in BALF to predict the acute exacerbation (AE) of chronic idiopathic interstitial pneumonias (IIPs). Methods. Two hundred and twenty-one patients with IIP diagnosed by bronchoscopy were enrolled in the study (IPF, n = 87; IIPs other than IPF, n = 134). Giemsa stain was used to detect HLMs in BALF specimens. Prussian blue stain was used to quantify HLMs in BALF, and a hemosiderin score (HS) was given to the specimens containing HLMs. Results. Twenty-four patients had a positive HS (range: 7‒132). The receiver-operating characteristic curve analysis identified the cutoff HS value for predicting the AE of IIPs to be 61.5. Seven cases had a higher HS (≥61.5) and 214 had a lower HS. AE occurred significantly earlier in the higher HS group (4/7 cases) than in the lower HS group (41/214 cases) during a median observation period of 1239 days (log-rank test, p = 0.026). Multivariate Cox proportional hazard regression analysis showed that a higher HS was a significant predictor of AE in addition to IPF, percent predicted forced vital capacity, and modified Medical Research Council score. The C-statistics for the prediction of AE did not significantly improve by all the above parameters with HS as compared without HS. Conclusions. A higher HS was a significant predictor of AE in IIPs but did not significantly improve the predictive ability of other parameters.